Potential financial impact on television networks of a ban on alcohol advertising during sports broadcasts in Australia - Florentine Martino; Jaithri Ananthapavan; Marj Moodie; Gary Sacks (Elsevier, 2022)
Abstract Objective: This study aimed to assess the potential financial impacts on Australian television networks of a ban on alcohol advertising during sports broadcasts. Methods: We analysed television advertising data from Nielsen, a commercial market research company. The data included details of all advertisements (ads) for the 10 highest‐spending alcohol brands on free‐to‐air television networks in the five largest capital cities in Australia over a 12‐month period (November 2018-October 2019). We estimated alcohol advertising spend during sports broadcasts. Financial value per network was estimated using ad duration and total spend per channel. Results: There were 10,660 alcohol ads (average of 75 minutes per week) shown during sports broadcasts, amounting to A$14.4 million in revenue to television networks. Forty‐five per cent of these ads were at children's viewing times. Channel Seven received the largest amount of alcohol advertising revenue (A$20.8 million), of which A$10.8 million (52.0%) was during sports broadcasts (0.5% of its total advertising revenue). Conclusions: Alcohol advertising during sports broadcasts is pervasive but contributes a relatively small proportion of revenue for television networks. Implications for public health: A ban on alcohol advertising during sport broadcasts is unlikely to have major financial impacts on broadcasters, whilst the health and social benefits are potentially substantial.